Penerapan Konsep Integrasi Berkas Rekam Medis di Rumah Sakit Umum Daerah Wates, Kulonprogo, Yogyakarta - Savitri Citra Budi (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
In Indonesia, under Law No. 44 of 2009 about Hospital, hospital has an obligation to organize medical records. Medical record is the file containing the notes and documents about the patient, examinations, treatments, actions, and other services that have been given to the patients (Regulation of Ministry of Health No. 269 of 2008 concerning Medical Record). Wates District Hospital has had a plan to change medical record storage from decentralized system to centralized one. One of the aims is obtained continuous patient’s medical history. Medical record must be prepared in such change. To implement the concept of integrated medical record by redesign of medical record forms in Wates District hospitals. The methods were carried out by following the design form concept, starting from collecting references, design, sources triangulation, first presentation, testing, revision, second presentasion, and the last was giving the design results to Wates District Hospital to be implemented. The application of the concept of integrated medical record was the new design of medical record forms consisting of a medical record folder, divider, emergency form, outpatient form, discharge summary form, resume form, inpatient approval form, informed consent form, and the newborn identification form.